Gallic Acid, a Promising Chemopreventive Agent, Antagonizes Breast Cancer: Molecular Mechanisms of Action from Cell Culture Studies - Hanaa H Ahmed (Journal of Global Pharma Technology, 2020)
Objective The present consideration converged on trailing the underlying molecular mechanism of gallic acid in striking the distinctly invasive breast cancer cell line; MDA-MB-231 in vitro. Methods The cytotoxic influence of gallic acid and 5-fluorouracil (5-FU) on MDA-MB-231 cells was stipulated by MTT assay. The expression levels of apoptosis, proliferation, progression, invasion and metastases-related genes were identified by RT-PCR. Results Our data specified that gallic acid and 5-FU displayed modest growth suppression with IC50 values of 251 and 367.171 µM contra MDA-MB-231 cells respectively after 48 h. Otherwise, treatment of MDA-MB-231 cells with gallic acid inspired significant downregulation in the expression level of survivin, STAT3, IL-6, VEGF, Slug, Snail, MMP7 and Notch-4 genes. Whereas, 5-FU instigated significant downregulation in the expression level survivin, STAT3, IL-6 and VEGF genes correlated with significant upregulation in the expression level of Snail and Notch-4 genes. Likewise, 5-FU provoked insignificant upregulation in the expression level of Slug and downregulation in the expression level MMP7 genes. Conclusion The attained data throw light on the distinct mechanism by which gallic acid could engage breast cancer. Gallic acid manifested chemopreventive potentiality against breast cancer aggressiveness through rectifying several dysregulated molecules implicated in cancer cell survival, proliferation, progression, angiogenesis, chemoresistance and metastasis.